Violência entre parceiros íntimos: um estudo sobre padrões de violência e correlatos psicossociais - Pereira, Isabele Negreiros de Queiroz (2025)
Intimate partner violence (IPV) is a highly prevalent and complex public health problem. It is estimated that the most common pattern of violence in romantic relationships involves aggression, whether proactive, reactive or defensive, by both partners. Thus, it is necessary to understand which factors contribute to the presence of violence in intimate relationships. In view of this, the present study proposed to explore to what extent psychosocial risk factors for IPV, specifically insecure anxious and avoidant attachment, attack and avoidance conflict resolution strategies, traditional gender norms, child maltreatment and emotional dysregulation influence the occurrence of patterns of violence between intimate partners, which were investigated through the analysis of latent classes based on different indicators of violence. To this end, this research is based on the socioecological model, considering the scientific and empirical literature on theoretical and etiological approaches to IPV. To achieve the above objective, 1021 adult participants who were in a romantic relationship were recruited, predominantly women (83.5%), white (64%) and heterosexual (58.1%). Sampling was by convenience (non-probabilistic). Participants answered an online questionnaire, disseminated through social media, containing the following self-report instruments: Difficulties in Emotion Regulation Scale – Short Form, Childhood Trauma Questionnaire – Short Form, Conflict Resolution Behavior Questionnaire, Gender-Equitable Men Scale, Revised Conflict Tactics Scale and sociodemographic questionnaire. The research was subject to approval by the Ethics Committee of the Federal University of Ceará- UFC (CAAE: 80188924.3.0000.5054), complying with the necessary ethical criteria. Data were analyzed using RStudio (version 2024.12.1) and Jamovi (version 2.6.26). Descriptive statistics, Spearman correlation analyses, latent class analysis and multinomial logistic regressions were performed. The psychosocial risk factors showed significant correlations in relation to the different forms of IPV, but with some specificities. Regarding the patterns of violence, three classes were identified, which were characterized respectively by low or no violence, bidirectional psychological violence and multiple forms of bidirectional violence. The most relevant risk factors in predicting the classes were the conflict resolution strategy of attack and anxious attachment. The avoidance strategy, avoidant attachment and difficulty in emotional regulation related to impulsivity also stood out. Although the present study had limitations, it is believed that its objectives were achieved and that its results can contribute significantly to the understanding of violence between intimate partners.